The Effect of Biorelevant Hydrodynamic Conditions on Drug Dissolution from Extended-Release Tablets in the Dynamic Colon Model - Connor O'Farrell; Mark J. H. Simmons; Hannah K. Batchelor; Konstantinos Stamatopoulos (MDPI AG, 2022)
The in vitro release of theophylline from an extended-release dosage form was studied under different hydrodynamic conditions in a United States Pharmacopoeial (USP) dissolution system II and a bespoke in vitro tubular model of the human colon, the Dynamic Colon Model (DCM). Five biorelevant motility patterns extracted from in vivo data were applied to the DCM, mimicking the human proximal colon under baseline conditions and following stimulation using polyethylene glycol or maltose; these represent the lower and upper bounds of motility normally expected in vivo. In the USPII, tablet dissolution was affected by changing hydrodynamic conditions at different agitation speeds of 25, 50 and 100 rpm. Applying different motility patterns in the DCM affected the dissolution profiles produced, with theophylline release at 24 h ranging from 56.74 ± 2.00% (baseline) to 96.74 ± 9.63% (maltose-stimulated). The concentration profiles of theophylline were markedly localized when measured at different segments of the DCM tube, highlighting the importance of a segmented lumen in intestine models and in generating spatial information to support simple temporal dissolution profiles. The results suggested that the shear stresses invoked by the unstimulated, healthy adult human colon may be lower than those in the USPII at 25 rpm and thus insufficient to achieve total release of a therapeutic compound from a hydroxyethyl cellulose matrix. When operated under stimulated conditions, drug release in the DCM was between that achieved at 25 and 50 rpm in the USPII.